2013
DOI: 10.1159/000350896
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Receptor Blockers Are Associated with Reduced Fibrosis and Interleukin-6 Expression in Calcific Aortic Valve Disease

Abstract: Background: Calcific aortic valve disease (CAVD) is a chronic disorder characterized by the mineralization of the aortic valve and involving fibrosis. Objectives: In this work we sought to determine if the fibrotic component of the remodeling process of CAVD was related to the use of angiotensin-converting enzyme inhibitors (ACEi) and/or angiotensin receptor blockers (ARBs). Methods: In 477 patients with CAVD, the aortic valve was examined by histology. A semiquantitative score of fibrosis was generated and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Côté et al found at least 25-fold variability in valve collagen among patients with severe aortic stenosis, and also found that about 20% of explanted valves demonstrated minimal valve collagen. 23 This new finding, taken together with studies in CAVS mice, demonstrates that mechanisms leading to severe aortic stenosis can be diverse in mice, as is the case in humans.…”
Section: Discussionmentioning
confidence: 80%
“…Côté et al found at least 25-fold variability in valve collagen among patients with severe aortic stenosis, and also found that about 20% of explanted valves demonstrated minimal valve collagen. 23 This new finding, taken together with studies in CAVS mice, demonstrates that mechanisms leading to severe aortic stenosis can be diverse in mice, as is the case in humans.…”
Section: Discussionmentioning
confidence: 80%
“…Hence, it is likely that compared with TAV, fibrosis is accentuated in BAV and alter valve haemodynamics significantly. In this regard, in 477 surgically explanted stenotic aortic valves, Côté et al 31 identified that BAV anatomy was independently associated with higher fibrosis score. In a small-size study, Ferda et al found a significant correlation between AVC and haemodynamic severity of AS but they did not find significant differences in AVC between BAV and TAV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, immunohistological analyses revealed in stenotic aortic valves that angiotensin II was present in the vicinity of mineralized nodules and colocalized with TNF- α and IL-6 [ 55 ]. Patients under a therapy with angiotensin receptor blockers (ARBs) have a lower level of transcript encoding for IL-6 in their aortic valves [ 56 ]. Moreover, a retrospective study showed that ARBs are associated with a slower progression rate of aortic stenosis [ 57 ].…”
Section: Nf-kappa B Pathway and Cavdmentioning
confidence: 99%